Analysis of tax evasion in the perspective of Islamic Economic Law - Ardhian, Ivan Rizal Nur (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to examine tax avoidance from an Islamic economic perspective. Halal efforts to reduce tax obligations through careful tax preparation are known as tax avoidance. However, in the context of Islamic economics, this step raises difficult moral and ethical issues related to the values ​​of social obligations, justice and honesty. This research uses a descriptive analysis approach combined with a qualitative approach. Through a literature review, consisting of books, journals and related articles, data was collected. The fundamentals of Islamic economics, including justice ('adl), benefit (maslahah), and balance (tawazun), were consulted during the investigation. Legally, tax evasion is not illegal. However, society and the state have been unfairly disadvantaged due to tax avoidance habits. Thus, their standards have been violated. Such actions have the potential to undermine public welfare and reduce government revenues intended for that purpose. Tax payments are seen as a social responsibility and a means to encourage sustainable economic growth from an Islamic economic perspective. As a result, tax avoidance is considered unethical and contrary to fundamental sharia behavior.